Fabrication, 3d finite element analysis and characterization of an optical passive microsensor - Braggio, Luciano (2013)
In this work we present the 3D Finite Element Analysis (FEA) of an optical passive microsensor for measuring pressure in biofluids and the simulation of the required characterization setup. Previously, we reported the design and analysis of a prototype where simulations were performed by using the Finite Element Method (FEM) in order to analyze the mechanical behavior of the grating;the results were exported to an optical software for diffraction analysis. The microsensor is based on a deformable diffraction grating made of an elastomeric polymer (PDMS); as the PDMS membrane containing the diffraction grating is subjected to a pressure, its optical properties are varied and an indirect measurement of the pressure is attainable. Now, we report the fabrication and characterization of the optical passive microsensor. The simulation of the setup required for characterization brings many advantages as it enables a rapid understanding of the optical properties of the microsensor without implementing it. Therefore, a correct model of both the optical and the mechanical model accelerates the development-time of the prototype so as to carry out possible re-designs in the future.